일부 초등학교 교사의 구강보건교육 인식에 영향을 미치는 요인 - 천혜원; Hyewon Cheon (Han'guk Ch'iwisaeng Hakhoe chi, 2015)
Objectives: The purpose of the study was to investigate the influencing factors on awareness toward oral health education in elementary school teachers. Methods: A self-reported questionnaire was completed by 250 elementary school teachers in Jeollado and Chungcheongdo from October 6 to November 28, 2014. The questionnaire consisted of the general characteristics of the subjects, oral health knowledge, oral health beliefs, and oral health education awareness measured by Likert 5 point scale. Cronbach alpha was 0.699 in the oral health knowledge and 0.957 in the oral health beliefs. Results: Those who were more interested in the oral health education had the awareness toward the necessity of oral health education. Those who had a longer career of education tended to have the strong beliefs in oral health education. Conclusions: The elementary school teachers are the most important persons in the lifelong oral health education facilitator to the students. It is very important to provide the continuing oral health education program development for the elementary school teachers.